Correlation between Maximum Oxygen Uptake with Pedalling Positions and Bicycle Speed - Martini, Tini; Rusdiana, Agus; Ray, Hamidie Ronald Daniel (Universitas Pendidikan Indonesia, 2020)
The purpose of this study was to investigate the relationship between VO2 Max pedalling positions, including sitting position and standing position toward speed. The samples in this study was ten junior athletes in DKI Jakarta. The research method used descriptive method. The instrument used to measure VO2 Max in this study was ergo cycle, while to track the speed, cyclo was used. Data analysis used SPSS version 20. The results of analysis and calculation of data displayed that VO2 max and the position of pedalling have a significant relationship with speed. Moreover, the position of standing pedalling is faster than the position of sitting pedalling. The results of this study are expected to give beneficial contributions in terms of training programs.AbstrakTujuan penelitian ini adalah untuk mengetahui korelasi antara VO2 Max pedaling posisi duduk dan berdiri terhadap kecepatan. Sampel dalam penelitian ini adalah sepuluh atlet junior DKI Jakarta. Metode penelitian yang digunakan adalah deskriptif. Instrumen yang digunakan pada penelitian ini menggunakan ergocycle untuk mengukur VO2 Max dan untuk mengukur kecepatan menggunakan cyclo. Analisis data menggunakan SPSS versi 20. Hasil analisis dan perhitungan data mengungkapkan bahwa VO2 max dan posisi pedaling memiliki hubungan yang signifikan terhadap kecepatan bersepeda, kemudian posisi pedalling berdiri lebih cepat dibandingkan dengan posisi pedaling duduk. Serta implikasi yang diharapkan dapat membantu dari segi program latihan.Â